2021
DOI: 10.3889/oamjms.2021.5602
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patellofemoral Measurement in Indonesian Population Using Magnetic Resonance Imaging

Abstract: BACKGROUND: The patellofemoral join is a unique complex joint formed by articulation of the patella and the femoral trochlea. Normal measures for patellofemoral parameters have been published. AIM: This study aimed to describe the characteristics of patellofemoral measurements in Indonesian population using magnetic resonance imaging (MRI). METHODS: This descriptive total sampling study was conducted from May 2019 to August 2020. The parameters of the measurements in this study include Insall-Salva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This finding is similar to the results of a study by Rhatomy et al (2021), who found no significant difference in patellar height between men and women using the Insall-Salvati and Caton-Deschamps methods. However, Hong et al (2020) found a significant difference in patellar height between men and women using the Insall-Salvati method [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is similar to the results of a study by Rhatomy et al (2021), who found no significant difference in patellar height between men and women using the Insall-Salvati and Caton-Deschamps methods. However, Hong et al (2020) found a significant difference in patellar height between men and women using the Insall-Salvati method [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, research on patellar height measurement has been carried out. This study describes the characteristics of patellar height measurement with MRI modality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%